2022
DOI: 10.3847/psj/ac3e66
|View full text |Cite
|
Sign up to set email alerts
|

Repeating Gas Ejection Events from Comet 45P/Honda–Mrkos–Pajdušáková

Abstract: Studying materials released from Jupiter-family comets (JFCs)—as seen in their inner comae, the envelope of gas and dust that forms as the comet approaches the Sun—improves the understanding of their origin and evolutionary history. As part of a coordinated, multiwavelength observing campaign, we observed comet 45P/Honda–Mrkos–Pajdušáková during its close approach to Earth in 2017 February. Narrowband observations were taken using the Bok 90″ telescope at Kitt Peak National Observatory on February 16 and 17 UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Another source of information about particle sizes of cometary dust is radar observations of cometary comae. Observations with the Arecibo observatory planetary radar system showed that the coma of comet 45P/H-M-P contains particles larger than 2 cm [53], while the existence of smaller particles could not be excluded. Single dust impacts in the size range of approximately r d ≈ 1 − 10 µm which likely originated from this comet were also identified in the dust dataset measured with the Helios spacecraft [16].…”
Section: Discussionmentioning
confidence: 98%
“…Another source of information about particle sizes of cometary dust is radar observations of cometary comae. Observations with the Arecibo observatory planetary radar system showed that the coma of comet 45P/H-M-P contains particles larger than 2 cm [53], while the existence of smaller particles could not be excluded. Single dust impacts in the size range of approximately r d ≈ 1 − 10 µm which likely originated from this comet were also identified in the dust dataset measured with the Helios spacecraft [16].…”
Section: Discussionmentioning
confidence: 98%
“…Each element has many strong emission lines in the visible range (specific colors in the color line). Any comet or rock that has a mixture of elements can be seen in its nucleus when it is directed at several wavelengths from a target [6][7][8], where each wavelength represents a different element received from each pixel of the image. This objective then shows the distributions of many elements on its surface.…”
Section: Introductionmentioning
confidence: 99%